Pendidikan Generasi Muda di PW GP Ansor Lampung - Fina Tri Nur Maharani; Izwah Marhamah; Rita Fatma Syafira; Ana Mentari; Rima Yuni Saputri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to observe the role of the Regional Leadership of the Ansor Youth Movement (PW GP Ansor) in Lampung in educating the younger generation, particularly in shaping character, leadership, and social engagement. Through direct observation and interviews with the chairman of PW GP Ansor Lampung, it was found that the organization actively fosters youth development through regular cadre training, leadership programs, religious-social activities, and creative economic empowerment initiatives. Despite facing challenges, especially in funding, PW GP Ansor Lampung strives to overcome them by establishing business units and collective livestock farms. The findings show that the organization plays a crucial role in instilling nationalism, religious values, and enhancing the social skills of youth in Lampung Province, thus creating innovative and transformative agents of change for society.